2020
DOI: 10.1159/000505929
|View full text |Cite
|
Sign up to set email alerts
|

Can Reflux Symptom Index and Reflux Finding Score Be Used to Guide the Treatment of Secretory Otitis Media in Adults?

Abstract: Background: At present more attention is paid to the treatment of secretory otitis media in children, but there is also a high incidence of adult patients. The etiology of secretory otitis media in adults is complex and related to many factors. Objectives: The aim of this study was to evaluate the correlation between the Reflux Symptom Index (RSI)/Reflux Finding Score (RFS) and secretory otitis media in adults, and to explore further treatment methods. Material and Methods: Taking outpatients in the otology de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This not only further proved that LPRD can be involved in the occurrence and progression of OME by affecting ET function, but also suggested that the simple RSI score could be used as a reference for anti-reflux therapy in adult OME patients. As the ET dysfunction evaluated by TMM method had been proved to be associated with ineffective conservative treatments ( 4 , 5 ), the clinical research conducted by Pang et al had proved the potential advantages of acid-suppressive drugs in OME patients with abnormal RSI results ( 22 ). Our results further suggested that the mechanism may be attributed to the prevention of LPRD in disrupting ET patency.…”
Section: Discussionmentioning
confidence: 99%
“…This not only further proved that LPRD can be involved in the occurrence and progression of OME by affecting ET function, but also suggested that the simple RSI score could be used as a reference for anti-reflux therapy in adult OME patients. As the ET dysfunction evaluated by TMM method had been proved to be associated with ineffective conservative treatments ( 4 , 5 ), the clinical research conducted by Pang et al had proved the potential advantages of acid-suppressive drugs in OME patients with abnormal RSI results ( 22 ). Our results further suggested that the mechanism may be attributed to the prevention of LPRD in disrupting ET patency.…”
Section: Discussionmentioning
confidence: 99%
“…Although we demonstrated significant findings, there are several limitations that should be considered in future research. First, GERD and chronic OME were identified only by the diagnostic code without information such as severity of reflux, reflux symptom index, reflux finding score, or physical examination findings [23] . However, we tried to improve the diagnostic accuracy of GERD by including patients who underwent at least one of the following tests: esophageal 24-hour pH monitoring, upper gastrointestinal endoscopy, and laryngoscopy, and who were prescribed anti-GERD medication for >4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Although we demonstrated significant findings, there are several limitations that should be considered in future research. First, GERD and chronic OME were identified only by the diagnostic code without information such as severity of reflux, reflux symptom index, reflux finding score or physical examination findings [23] . However, we tried to improve the diagnostic accuracy of GERD by including patients who underwent at least one of the following tests: esophageal 24-hour pH monitoring, upper gastrointestinal endoscopy, and laryngoscopy, and who were prescribed anti-GERD medication for more than 4 weeks.…”
Section: Discussionmentioning
confidence: 99%